Perception of emotionally loaded vocal expressions and its connection to responses to music. A cross-cultural investigation: Estonia, Finland, Sweden, Russia, and the USA - Waaramaa, Teija; Leisiö, Timo (Frontiers in Psychology, 2013)
The present study focused on voice quality and the perception of the basic emotions from speech samples in cross-cultural conditions. It was examined whether voice quality, cultural or language background, age or gender were related to the identification of the emotions. Professional actors (n2) and actresses (n2) produced nonsense sentences (n32) and protracted vowels (n8) expressing the six basic emotions, interest and a neutral emotional state. The impact of musical interests on the ability to distinguish between emotions or valence (on an axis positivity – neutrality – negativity) from voice samples was studied. Listening tests were conducted on location in five countries: Estonia, Finland, Russia, Sweden and the USA with 50 randomly chosen participants (25 males and 25 females) in each country. The participants (total N=250) completed a questionnaire eliciting their background information and musical interests. The responses in the listening test and the questionnaires were statistically analysed. Voice quality parameters and the share of the emotions and valence identified correlated significantly with each other for both genders. The percentage of emotions and valence identified was clearly above the chance level in each of the five countries studied, however, the countries differed significantly from each other for the identified emotions and the gender of the speaker. The samples produced by females were identified significantly better than those produced by males. Listener’s age was a significant variable. Only minor gender differences were found for the identification. Perceptual confusion in the listening test between emotions seemed to be dependent on their similar voice production types. Musical interests tended to have a positive effect on the identification of the emotions. The results also suggest that identifying emotions from speech samples may be easier for those listeners who share a similar language or cultural background with the speaker.